Testing the affective events theory in hospitality management: A multi-sample approach - Junça Silva, A.; Lopes, E. R. (Sustainability, 2023)
Relying on the affective events theory, we argued that daily micro-events occurring in a hospitality context—daily hassles and uplifts—would influence hotel employees’ well-being and performance through affective reactions. Furthermore, we also expected that mindfulness would moderate these indirect relationships. Data were collected from employees who worked in hospitality working settings, and included both mindfulness practitioners (n = 182) and non-practitioners (n = 211). The findings evidenced that affective reactions mediated the path from daily micro-events and well-being and performance, in both samples. In addition, in the sample of non-mindfulness practitioners, mindfulness moderated the indirect relationship between daily micro-events and well-being through affective reactions, in such a way that the relationship became stronger for those who scored higher on mindfulness (versus those who scored lower). These findings were not significant for those who practiced mindfulness. Lastly, mindfulness did not moderate the relationship between daily micro-events and performance via affective reactions (for both samples). This study expands the affective events theory for the hospitality context and thus highlights the role of daily micro-events in stimulating employees’ performance and well-being. Furthermore, it shows how mindfulness as a trait may be relevant for employees who work in this context.